Verification and application of a modified carbapenem inactivation method (mCIM) on Pseudomonas aeruginosa: a potential screening methodology on carbapenemases phenotype in Bacillus cereus. Issue 5 (2nd May 2022) - Liu, Junyan; Lin, Xin; Bai, Caiying; Soteyome, Thanapop; Bai, Xiaoxi; Wang, Juexin; Ye, Congxiu; Fan, Xiaoyi; Liu, Juzhen; Huang, Yunzu; Liu, Liyan; Xu, Zhenbo; et al.
ABSTRACT: Antimicrobial resistance (AMR) has been a leading issue for human health globally threatening the achievement of several of the Sustainable Development Goals (SDGs). Originated from Bacillus cereus, carbapenemases phenotype has been considered to be a major concern in AMR. In this study, the AMR identification rate of P. aeruginosa isolates and infections in FAHJU showed an obvious upward trend from 2012 to 2016. All 88 carbapenem-resistant P. aeruginosa strains were screened for carbapenemase phenotype by modified Carbapenem Inactivation Method (mCIM), and these results of mCIM were compared with traditional PCR results. The isolates of P. aeruginosa and infected patients showed obvious upward trend from 2012 to 2016. The drug resistance to common clinical antibiotics was serious that the clinical rational use of antibiotics should be strengthened, which is in accordance with the Global Antimicrobial Resistance and Use Surveillance System (GLASS) report. In comparison, the results of mCIM showed that 18 out of 88 CRPA strains were carbapenemase positive, which were completely consistent with the results yielded by PCR method. Therefore, it is convinced that this mCIM methodology is a simple and quick method for detected carbapenemases producing P. aeruginosa and has a potential capability in carbapenemases phenotype of pathogen like B. cereus, which will undoubtedly aid in the AMR therapy. Graphical abstract:Interpretation standards of modified carbapenem inactivation method: uf0001